Amino-terminal pro-brain natriuretic peptide and the red cell distribution width as a prognostic factor of severity in patients with acute decompensated heart failure - León-Castillo, Brunela (2023)
Introduction: The study of predictors of negative outcomes in patients with heart failure has included the combination of natriuretic peptides and red cell distribution width (RDW). Objective: To evaluate the combined use of the amino-terminal pro-brain natriuretic peptide (NT-proBNP) and RDW as a prognostic factor for death from any cause, prolonged hospitalization, and readmission one year after discharge in patients with decompensated acute heart failure (AHF). Methods: We conducted a retrospective observational study. We constructed a combined index = NT-ProBNP x RDW/100. ROC curves were constructed, sensitivity and specificity were estimated based on the cut-off points, and the relative risk was estimated to develop the outcomes studied. We compared the area under curve of combined index versus NT-proBNP and RDW, separately. Results: We analyzed data from 471 patients. The combined index had its best cut of 927.79 to predict death during the first year of admission. Those with values ≥ 927,79 had a relative risk of 32.7 (95% CI: 4.8 – 222.3). To predict hospitalization ≥7 days, the cut-off point was 752.67; those with this value or higher had a relative risk of 22.4 (95% CI: 9.7 – 51.8). To predict readmission one year after discharge, the cutoff was 858.47 and the relative risk was 4.7 (95% CI: 3.3 – 6.8). Conclusions: The combined index used generate relative risks that show a strong strength of association for death from any cause, hospitalization ≥7 days, and readmissions one year after discharge. However, the superiority to discriminate was inconclusive with respect to the individual components.